1987
DOI: 10.1104/pp.85.1.273
|View full text |Cite
|
Sign up to set email alerts
|

Control of Wild Carrot Somatic Embryo Development by Antioxidants

Abstract: ABSTRACrAs we previously reported for glutathione (GSH), both ascorbic acid (AA) and vitamin E were observed to suppress wild carrot (Daucus carota L.) somatic embryogenesis with little concomitant effect on biomass.Endogenous concentrations of AA were lower during embryo development than during cell proliferation, exhibiting a temporal pattern nearly identical to that of GSH. GSSG (oxidized GSH) MATERIALS AND METHODS Cell Culture. Wild carrot (Daucus carota L.) cell suspensions were grown proliferatively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…However, the interaction between antioxidant status and in-vitro morphogenesis may be quite complex, especially when manipulated by exogenous hormones. Earnshaw and Johnson (1987) report that somatic embryogenesis in wild carrot can be suppressed by the addition of glutathione, ascorbate and vitamin E, and that the concentration of the former two compounds can be affected by the presence of 2,4-D. Whilst this study provides evidence that a lowering of certain antioxidants is necessary for embryo development it is important to note that development is a dynamic process. The redox requirements necessary for the maintenance of embryogenic potential may be quite different from those required for embryo development per se.…”
Section: Discus~onmentioning
confidence: 65%
“…However, the interaction between antioxidant status and in-vitro morphogenesis may be quite complex, especially when manipulated by exogenous hormones. Earnshaw and Johnson (1987) report that somatic embryogenesis in wild carrot can be suppressed by the addition of glutathione, ascorbate and vitamin E, and that the concentration of the former two compounds can be affected by the presence of 2,4-D. Whilst this study provides evidence that a lowering of certain antioxidants is necessary for embryo development it is important to note that development is a dynamic process. The redox requirements necessary for the maintenance of embryogenic potential may be quite different from those required for embryo development per se.…”
Section: Discus~onmentioning
confidence: 65%
“…Besides hormonal supplementations in the culture medium, another important factor regulating embryogenesis in both animal and plant systems is the cellular redox state (Earnshaw and Johnson 1987, Gardiner et al 1998, Shi et al 2000, Stasolla et al 2004, Belmonte et al 2005). Alterations of the endogenous glutathione redox status [defined as the ratio of the concentration of the reduced form (GSH) to the concentration of the oxidized plus reduced forms (GSSG + GSH)] delineate specific stages of embryo development both in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Cui et al (1999) and Gupta andDatta (2003/2004) showed that an addition of H 2 O 2 to culture medium resulted in an increase of frequency of somatic embryogenesis in L. barbarum and G. hybridus. Antioxidants have been shown to suppress somatic embryo formation in culture of wild Daucus carota (Earnshaw and Johnson 1987). Taking it into consideration, it may not be ruled out that the enhancement of H 2 O 2 production in the sunflower embryos maintained for 1 day on EIM may be a part of signalling cascade leading to somatic embryo induction.…”
Section: Discussionmentioning
confidence: 99%